The impact of non-lethal doses of pyriproxyfen on male and female Aedes albopictus reproductive fitness - Kancharlapalli, Sri Jyosthsna; Brelsfoard, Corey L. (Frontiers in Insect Science, 2024)
Introduction: Control of the mosquito Ae. albopictus is confounded by the behavior of this mosquito because females prefer to oviposition in small natural and artificial containers that are often difficult to remove or treat with insecticides. Autodissemination strategies utilizing highly potent insect growth regulators (IGR) have emerged as promising tools for the control of this container-inhabiting species. The intended goal of autodissemination approaches is to use mosquitoes to self-deliver an IGR to these cryptic oviposition locations. Previous studies have focused on the efficacy of these approaches to impact natural populations, but little focus has been placed on the impacts on mosquitoes when exposed to non-lethal doses of IGRs similar to the levels they would be exposed to with autodissemination approaches.Methods: In this study, the impact of non-lethal doses of pyriproxyfen (PPF) on Ae. albopictus reproductive fitness was investigated. Ae. albopictus female and male mosquitoes were exposed to nonlethal doses of pyriproxyfen and their fecundity and fertility were measured. To examine the impact of non-lethal doses of PPF on the expression of ecdysone-regulated genes USP, HR3, and Vg involved in vitellogenesis was measured.Our results demonstrate a significant reduction in female fecundity, blood feeding rates, and egg hatch rates when exposed to non-lethal doses of PPF. Oocyte development was also delayed in PPFtreated females. Furthermore, exposure to non-lethal doses of PPF altered the expression of genes involved in vitellogenesis, indicating disruption of hormonal regulation. Interestingly, PPF exposure also reduced sperm production in males, suggesting a potential semi-sterilization effect.Discussion: These findings suggest that non-lethal doses of PPF could enhance the efficacy of autodissemination approaches by impacting both male and female reproductive fitness. However, further research is needed to validate these laboratory findings in field settings and assess their practical implications for vector control strategies.